A atuação do/a assistente social no Centro de Referência Especializado de Assistência Social da cidade do Guarujá-SP: ensaios sobre a execução do projeto de trabalho profissional - Gouveia, Felipe de Oliveira (2022)
The present dissertation aims to analyze the execution of the professional work project of the social worker at the Specialized Reference Center for Social Assistance (CREAS) in the city of Guarujá-SP, and possible mimetic relationships between professional attribution versus actions described in the Policy of Social Assistance. Social assistance. It analyzes the new configurations of the world of work that have a seat in the mature society of capital, which has been faced with the constant deepening of social inequality caused by the capitalist system in its new societal order. The multiple violations of rights take place in the midst of the deepening of the social question, with the State having the primary role as provider of social and citizenship rights. It is in this socio-technical division of work that the social worker will work. In his condition as a salaried worker, in the sale of his work force in favor of the class that lives from work, confronting the State in the face of the existential absences of distributive social protection. In this sense, a bibliographic and documentary survey of the specialized literature on the subject was carried out, aiming to understand the empirical phenomenon that proved to be the object of analysis of this study. The focus of the research was directed to the Single Social Assistance System (SUAS), with a focus on the services of the Specialized Reference Center for Social Assistance in the city of Guarujá-SP. The research is based on a qualitative methodology, document analysis, literature, statistical data and semi-structured interviews with eleven (11) social workers employed by the public administration of the municipal government of Guarujá, assigned to the state unit of CREAS. In this universe, it was allowed to process the relationship between the specific work of the social worker and the actions described in the Social Assistance Policy. Among the research findings, the transmutation of the work of the social worker by the described actions of the social assistance policy arising from the existing reductionism between professional training and the precariousness of the social assistance policy and its regulations, in this case, where it appears the mimetic relationship between profession and public policy is established. As well as the personification of the denial of social rights by the State in the figure of the social worker for mediating this relationship with the user citizen when the offers do not exist, causing the ethical-political suffering of this worker who sees in the absence of the State an impotence, and in this way, the suffering of the citizen user of social assistance services who is placed on the sidelines of their citizenship rights also increases